Kepuasan Pelanggan, Kualitas Produk, dan Nilai yang Dirasakan: Mengukur Loyalitas Konsumen di Warung Kopi Kota Langsa - Aminullah Abd. Aziz; Agustinar agustinar; M. Yahya; Nur Azizah (JIM: Jurnal Ilmiah Mahasiswa, 2023)
Product quality, perceived value on consumer loyalty in choosing a coffee shop in Langsa City. The research method used in this study was the sampling method carried out by the Accidental Sampling method, namely determining the sample based on the people you met. by chance or anyone who is consuming coffee in a coffee shop. In this study, the number of samples determined by the researcher was 35 respondents. The data collection method uses interview techniques and the instrument used is a questionnaire. The instrument has met the validity requirements with a reliability coefficient (Crombach's Alpha) of 0.571, 0.638, 0.433 and 0.652 respectively for Determination is used to measure how far the variable ability of customer satisfaction is product quality, perceived value and loyalty variables. Data analysis was carried out using qualitative methods and quantitative methods with the formulas namely Regression Analysis, T-test, F-test and Coefficient of Determination Test (R2) with the help of SPSS 16 software for windows. The results showed that the variable customer satisfaction t-count < t-table (0.514 < 1.697) so that it can be concluded that the variable customer satisfaction has no significant effect on customer loyalty. product quality variable t-count > t-table (6.28 > 1.697) so that it can be concluded that product quality variables have a significant effect on consumer loyalty. perceived value variable t-count <t-table (0.255 <1.697) so it can be concluded that perceived value variable has no significant effect on consumer loyalty.